-9(-2)+2y=-18

Simple and best practice solution for -9(-2)+2y=-18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9(-2)+2y=-18 equation:


Simplifying
-9(-2) + 2y = -18

Multiply -9 * -2
18 + 2y = -18

Solving
18 + 2y = -18

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-18' to each side of the equation.
18 + -18 + 2y = -18 + -18

Combine like terms: 18 + -18 = 0
0 + 2y = -18 + -18
2y = -18 + -18

Combine like terms: -18 + -18 = -36
2y = -36

Divide each side by '2'.
y = -18

Simplifying
y = -18

See similar equations:

| 4(n-14)=16 | | 9y-7y-11=22.36 | | 60(2/5x) | | 1/3x^2-20=55 | | -9x+2y=-18 | | x(7)-4=11 | | (125x-30)/(125x-20)=0.857 | | -4(x)-6=14 | | 4/4b+b/2-6/2=12/8 | | -3(x+4)-9=-2x+12 | | -3x(x+4)-9=-2x+12 | | -2/3y=18 | | 2x=17.5 | | 10(-6)-6y=-60 | | 342=12x-13x+2 | | 342=12x-13x+12 | | =3x^2-150x+1250 | | =3x^2-150+1250 | | 9*0-9y=-81 | | 3/12n=15/6 | | 9x*9y=-8 | | 9x-9y=-81 | | 12x+6=349-28 | | y=-1/7x+12/7 | | 4(3t+-2)+3-89=89 | | 4(3+-2)+3-89=89 | | -4*0-8y=32 | | -6(0)-8y=48 | | 3p+5q-6(3p-3q+3r)= | | -4-8y=32 | | 0.35t^2-50t+1000=0 | | 0.05*t^2+54*t-500=0 |

Equations solver categories